Interrelationships among invasive and non-invasive indicators of biological maturation in adolescent male soccer players - Malina, R. M.; Coelho e Silva, M. J.; Figueiredo, A. J.; Carling, C.; Beunen, G. P. (Journal of Sports Sciences, 2012)
The relationships among indicators of biological maturation were evaluated and concordance between classifications of maturity status in two age groups of youth soccer players examined (11-12 years, n=87; 13-14 years, n=93). Data included chronological age (CA), skeletal age (SA, Fels method), stage of pubic hair, predicted age at peak height velocity, and percent of predicted adult height. Players were classified as on time, late or early in maturation using the SA-CA difference, predicted age at peak height velocity, and percent of predicted mature height. Factor analyses indicated two factors in players aged 11-12 years (maturity status: percent of predicted mature height, stage of pubic hair, 59% of variance; maturity timing: SA/CA ratio, predicted age at peak height velocity, 26% of variance), and one factor in players aged 13-14 years (68% of variance). Kappa coefficients were low (0.02?0.23) and indicated poor agreement between maturity classifications. Spearman rank-order correlations between categories were low to moderate (0.16?0.50). Although the indicators were related, concordance of maturity classifications between skeletal age and predicted age at peak height velocity and percent predicted mature height was poor. Talent development programmes call for the classification of youth as early, average, and late maturing for the purpose of designing training and competition programmes. Non-invasive indicators of maturity status have limitations for this purpose.